Patient and Physician Preferences for Antibiotics in Acute Uncomplicated Diverticulitis: A Delphi Consensus Process to Generate Noninferiority Margins. Issue 1 (January 2021) - Garfinkle, Richard; Sabboobeh, Sarah; Demian, Marie; Barkun, Alan; Boutros, Marylise
Abstract : BACKGROUND: Despite the existing evidence, the omission of antibiotics in the management of acute uncomplicated diverticulitis has not gained widespread acceptance. OBJECTIVE: This study aims to incorporate the input of both patients and physicians on the omission of antibiotics in uncomplicated diverticulitis to generate noninferiority margins for 3 outcomes. DESIGN: This was a mixed-methods study, including in-person interviews with patients and a Delphi process with physicians. SETTINGS: North American patients and physicians participated. PATIENTS: Consecutive patients undergoing colonoscopy, 40% of whom had a previous history of diverticulitis, were selected. INTERVENTIONS: Informational video (for patients) and evidence summaries (for physicians) regarding antibiotics in diverticulitis were reviewed. MAIN OUTCOMES MEASURES: Noninferiority margins were generated for time to reach full recovery, persistent diverticulitis, and progression to complicated diverticulitis in the context of a nonantibiotic strategy. Consensus was defined as an interquartile range <2.5. RESULTS: Fifty patients participated in this study. To avoid antibiotics, patients were willing to accept up to 5.0 (3.0–7.0) days longer to reach full recovery, up to an absolute increase of 4.0% (4.0–6.0) in the risk of developing persistent diverticulitis, and up to an absolute increase of 2.0% (0–3.8) in the risk of progressing to complicated diverticulitis. A total of 55 physicians participated in the Delphi (round 1 response rate = 94.8%; round 2 response rate = 100%). Consensus noninferiority margins were generated for persistent diverticulitis (4.0%, 4.0–5.0) and progression to complicated diverticulitis (3.0%, 2.0–3.0), but could not be generated for time to reach full recovery (5.0 days, 3.5–7.0). LIMITATIONS: Patients were recruited from a single institution, and Delphi participants were invited and not randomly selected. CONCLUSION: Noninferiority margins were generated for 3 important outcomes after the treatment of acute uncomplicated diverticulitis in the context of a nonantibiotic strategy. Abstract : Supplemental Digital Content is available in the text.